PERFORMANCE ANALYSIS OF WIRELES ON THE GROWTH OF USERS OF SEA TRANSPORTATION SERVICES IN HUNIMUA PORT - CENTRAL MALUKU - Ohorella, Fuad Hasan; Latuconsina, Syarifudin Ishak; Palaklely, Rayleky (Fakultas Teknik Universitas Tanjungpura, 2023)
Hunimua Harbor is the link between Ambon Island and Seram Island. The flow of growth in sea transportation users at Hunimua Port in the last five years has increased. The preliminary analysis of Hunimua Port shows that in 2021 passenger growth is 21%, 2-wheeled vehicle growth is 17%, 4/6-wheeled growth is 24%, and ship visit growth is 5%, respectively, and Berth Occupancy Ratio (BOR) is 72%. The results showed that the average annual load growth over the next ten years was 1.7% for passengers, 1.2% for R-2 vehicles, and 4.5% for R-4/6 vehicles. The Load Factor in 2026 has reached 68%, and in 2031 it has born 67%, which means that the level of demand for ferry transportation has exceeded the available capacity, based on the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 104 of 2017 concerning the Implementation of Ferry Transportation. The Berth Occupancy Ratio (BOR) value for 2026 = 82%, and in 2031 = 92%. From the percentage of BOR values in table 2.1 based on UNCTAD standards, Hunimua Port should have more than six piers ready to operate in 2026.